Programmed cell death ligand-1 expression and survival in a cohort of patients with non-small cell lung cancer receiving first-line through third-line therapy in Denmark. (August 2021) - Hedgeman, Elizabeth; Nørgaard, Mette; Dalvi, Tapashi; Pedersen, Lars; Hansen, Hanh Pham; Walker, Jill; Midha, Anita; Shire, Norah; Boothman, Anne-Marie; Fryzek, Jon P.; Rigas, James; Mellemgaard, Anders; et al.
Highlights: Large population-based cohort study of Danish patients with NSCLC. No association between PD-L1 expression on tumor cells ≥25 % and overall survival. PD-L1 expression on immune cells suggests survival advantage in second-line setting. Abstract: Background: PD-L1 expression on tumor cells (TCs) or immune cells (ICs) may be used as a prognostic marker for survival in patients with NSCLC. We characterized PD-L1 expression on TCs or ICs in a patient cohort with NSCLC to determine associations between PD-L1 expression and overall survival (OS), according to EGFR and KRAS mutation status. Methods: Danish patients aged >18 years diagnosed with NSCLC before 2014 on first- (N = 491), second- (N = 368), or third-line (N = 498) therapy were included. Data were extracted from population-based medical registries. Tumor samples from pathology archives were tested for biomarkers. High PD-L1 expression was defined as expression on ≥25 % of TCs or ICs based on first diagnostic biopsy or surgical resection. KRAS and EGFR mutation status were tested using PCR-based assays. Cox regression analysis was used to compute adjusted HRs and associated 95 % CIs. Results: PD-L1 TC and IC ≥ 25 % were observed in 24.3 %–31.0 % and 11.7–14.7 % of patients, respectively. EGFR and KRAS mutations were detected in 4.7 %–8.8 % and 26.5 %–30.7 % of patients, respectively. PD-L1 TC ≥ 25 % was not associated with survival advantage in first- (HR = 0.96, 95 % CI: 0.75–1.22), second- (1.08, 0.81–1.42), or third-line (0.94, 0.74–1.20) therapy. PD-L1 IC ≥ 25 % was associated with survival advantage in second-line (HR = 0.56, 95 % CI: 0.36–0.86) and third-line (0.69, 0.49–0.97) but not first-line (1.00, 0.70–1.41) therapy. Conclusion: No association was observed between PD-L1 TC ≥ 25 % and OS in any therapy line. PD-L1 IC ≥ 25 % may confer survival benefit among some patients who reach second-line therapy.